Human cognition and social agent technology - Dautenhahn, Kerstin (Advances in consciousness research, 2000)
Human Cognition and Social Agent Technology is written for readers who are curious about what human (social) cognition is, and whether and how advanced software programs or robots can become social agents. Topics addressed in 16 peer-reviewed chapters by researchers at the forefront of agent research include: Narrative intelligence and implementations of story-telling systems, socially situated avatars and 'conscious' software agents, cognitive architectures for socially intelligent agents, agents with emotions, design issues for interactive systems, artificial life agents, contributions to ag.